High Temperature Synthesis and Characterization of Hydroxyapatite Doped with Silver Nanoparticles - SADJADI*, M.S.; EBRAHIMI AFARANI, H.R.; ZARE†, K. (Asian Journal of Chemistry, 2024)
Calcium hydroxyapatite, is a material which is closely resembleswith bone apatite and exhibits excellent osteoconductivity. In this work,the synthesis of hydroxyapatite in a modified synthetic body fluid (SBF)solutions at 37 °C and pH of 7.4 was performed using novel chemicalprecipitation technique. Then after heat operation at 1200 ºC, on filteredprecipitated result calcium hydroxyapatite were produced. Hydroxyapatitedoped with silver nanoparticles was prepared by treatment withAgNO3 solution and reduction of Ag+ ions by sodium borohydratesolution. The formations of the silver nanoparticles on the calcium hydroxyapatitestructure were confirmed by X-ray diffraction and transmissionelectron microscopy. Transmission electron microscopy image showsthe nanostructure of silver particles, being formed on hydroxyapatitetexture.